Pelatihan Kader Perencanaan Sehat sebagai Penggerak Edukasi Pra-Konsepsi di Dusun Olat Rarang Desa Labuhan Sumbawa - Fitri Setianingsih; Ninik Wahyuni; Galuh Permatasari; Nurlaila Agustikawati (Jurnal Informasi Pengabdian Masyarakat, 2026)
Pre-conception health planning is essential for maternal and child health quality, yet public awareness in rural areas remains low. This community service aims to establish and optimize the role of the "Healthy Planning Cadre" as driving agents for pre-conception education in Olat Rarang Hamlet, Labuhan Village, Sumbawa. Methods: The program used a Participatory Community Development approach involving 10 local health cadres. The intervention consisted of three phases: coordination & preparation, interactive educational training (covering nutrition, health screening, and mental readiness), and evaluation via pre-test and post-test. Results: The training successfully produced 10 certified "Healthy Planning Cadres" equipped with pre-conception counseling skills. Evaluation data showed a significant increase in cadres' knowledge, with the average score rising from 62.5 (pre-test) to 88.0 (post-test), indicating an improvement of 25.5 points. Cadres also demonstrated proper counseling techniques during roleplay simulations. Conclusion: Empowering grassroots health cadres through culturally close approaches is effective in improving maternal health promotion sustainability. Regular monitoring from local primary health centers is recommended to maintain the cadres' performance in reducing stunting and pregnancy complications.